A fuzzy logic based risk assessment approach for evaluating and prioritizing risks in cloud computing environment - Amini A.; Jamil N.; Ahmad A.R.; Sulaiman H. (Springer Science and Business Media Deutschland GmbH, 2023)
Cloud computing; Computer circuits; Fuzzy logic; Numerical methods; Risk management; Risk perception; Security of data; Assessment approaches; Business environments; Cloud computing environments; Conceptual model; Management efforts; Numerical values; On-demand services; Quantitative data; Risk assessment